Composite solid electrolyte and battery using the same

A composite solid electrolyte with a three-dimensional network structure of inorganic sulfide and conductive polymer addresses adhesion and stability issues in sodium ion batteries, enhancing conductivity and stability.

JP2025009182APending Publication Date: 2025-01-20NAT UNIV CORP KYUSHU INST OF TECH (JP)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023112002
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing sodium ion batteries face issues with low adhesion between electrodes and solid electrolytes, leading to gaps and mechanical instability, and current solid electrolytes suffer from low ionic conductivity and stability problems.

Method used

A composite solid electrolyte comprising an inorganic sulfide material with sodium ions and a conductive polymer forms a three-dimensional network structure, coating the inorganic sulfide material's surface with the polymer to enhance adhesion and stability.

Benefits of technology

The composite electrolyte achieves low interfacial resistance, high conductivity, and excellent stability due to the synergistic effect of the inorganic sulfide material and conductive polymer, enabling high-performance sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009182000001_ABST
    Figure 2025009182000001_ABST
Patent Text Reader

Abstract

To provide a solid electrolyte having advantages of both a sulfide-based solid electrolyte improved in ionic conductivity and a polymer-based solid electrolyte improved in stability.SOLUTION: A composite solid electrolyte contains an inorganic sulfide material containing sodium ions and having ionic conductivity, and a conductive polymer. In the composite solid electrolyte, the specific inorganic sulfide material and the conductive polymer form a three-dimensional structure. The composite solid electrolyte obtained as a result has a form in which a surface of the inorganic sulfide material is coated and protected with the conductive polymer. As a result, the composite solid electrolyte has low interface resistance, high conductivity and excellent stability because of synergetic effect of the inorganic sulfide material and the conductive polymer.SELECTED DRAWING: Figure 1(b)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel composite solid electrolyte and a battery using the same. [Background technology]

[0002] Since secondary batteries have excellent energy density and power density and are effective in reducing size and weight, the demand for them as power sources for portable devices such as notebook computers, tablet terminals, mobile phones, and handheld video cameras is growing rapidly. Secondary batteries are also attracting attention as power sources for electric vehicles and power load leveling.

[0003] Lithium-ion batteries are currently the mainstream secondary battery. However, lithium is a rare metal and is not suitable for making large-capacity secondary batteries. For this reason, sodium-ion batteries have been attracting attention. Sodium is an abundant resource, occurring in seawater and 2-3% of the earth's crust, and has the advantage of being inexpensive to obtain as a raw material. In addition, sodium-ion batteries have the advantages of having a larger storage capacity than lithium-ion batteries, a much faster charging speed than lithium-ion batteries, and a wider operating temperature range. For this reason, sodium-ion batteries have been attracting attention as a candidate for future secondary batteries. On the other hand, currently proposed sodium-ion batteries use liquid electrolytes containing organic solvents. Sodium ions in liquid electrolytes have low resistance and can move freely, making it easy to achieve interfacial contact between the electrodes and the electrolyte. On the other hand, liquid electrolytes pose a risk of fire, etc.

[0004] In recent years, development of batteries using solid electrolytes instead of electrolyte solutions has been progressing. Known solid electrolytes used in solid batteries include inorganic solid electrolytes such as sulfide-based or oxide-based electrolytes, and polymer-based solid electrolytes, and solid batteries using these electrolytes have been studied. Here, solid batteries using solid electrolytes have problems such as the inability to adhere the electrodes to the solid electrolyte, and the low water resistance of the solid electrolyte. If the adhesion is low, the positive and negative electrodes shrink and expand when the battery is charged and discharged, and a gap gradually forms between the electrodes and the electrolyte.

[0005] Among these solid electrolytes, those that use sulfides as the main raw material have higher ionic conductivity than those that use oxides as the main raw material. However, solid sulfides have the problem that they generate toxic hydrogen sulfide gas through oxidative decomposition or reaction with water, which causes deterioration of the battery.

[0006] In contrast, polymer-based solid electrolytes have excellent thermal and chemical stability, but they have problems with low ionic conductivity and stability.

[0007] Therefore, attempts have been made to improve sulfide-based solid electrolytes (see, for example, Patent Document 1). For example, Patent Document 1 discloses an electrolyte composition that uses a sulfide-based solid electrolyte and a polymer whose glass transition temperature or melting point is equal to or lower than a specific temperature, with the aim of providing an electrolyte composition that can realize a battery with excellent ion conductivity. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2022-145417 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, the electrolyte composition described in Patent Document 1 cannot solve the problems associated with the electrolytes using sulfides as the main raw material and the polymer-based solid electrolytes described above.

[0010] Therefore, an object of the present invention is to provide a solid electrolyte having the advantages of both a sulfide-based solid electrolyte having excellent ionic conductivity and a polymer-based solid electrolyte having high stability. [Means for solving the problem]

[0011] As a result of intensive research to solve the above problems, the present inventors have found that the above problems can be solved by using a composite solid electrolyte containing a specific inorganic sulfide material and a conductive polymer, and have completed the present invention. That is, the present invention is as follows.

[0012] The composite solid electrolyte of the present invention comprises an inorganic sulfide material having ionic conductivity including sodium ions and a conductive polymer.

[0013] The composite solid electrolyte of the present invention is a composite of a specific inorganic sulfide material and a conductive polymer. The composite solid electrolyte of the present invention has a three-dimensional (3D) network structure. The obtained composite solid electrolyte is in a form in which the surface of the inorganic sulfide material is coated with a conductive polymer and protected. As a result, the composite solid electrolyte of the present invention has low interfacial resistance, high conductivity, and excellent stability due to the synergistic effect of the inorganic sulfide material and the conductive polymer.

[0014] In the composite solid electrolyte of the present invention, the inorganic sulfide material having ion conductivity containing sodium ions may contain Na-PS elements.

[0015] In the composite solid electrolyte of the present invention, the inorganic sulfide material having ion conductivity containing sodium ions may be a composite solid electrolyte that is a compound represented by the following formula (I):

[0016] NaM1M2PS····(I) In the formula, M1 and M2 are III-VI transition metals and 13-15 group metals. The compound represented by formula (I) contains 2-3 kinds of metals. As a result, a composite solid electrolyte with high ionic conductivity can be obtained.

[0017] In the composite solid electrolyte of the present invention, the compound represented by the formula (I) may be a compound represented by the following formula (I'):

[0018] Na x M1 p M2 q P.S. y ...(I´) In formula (I'), x and y are numbers that satisfy 3≦x≦17 and 2≦y≦14, respectively. In addition, p and q are numbers that satisfy 0.01≦p≦10 and 0.001≦q≦10, respectively.

[0019] In the composite solid electrolyte of the present invention, the conductive polymer may be a polymer having a polyethylene oxide main skeleton or a polyvinylidene fluoride resin.

[0020] The composite solid electrolyte of the present invention may be a three-dimensional structure of an inorganic sulfide material and a conductive polymer.

[0021] The battery of the present invention comprises any one of the composite solid electrolytes described above. Effect of the Invention

[0022] The composite solid electrolyte of the present invention includes an inorganic sulfide material having ionic conductivity including sodium ions and a conductive polymer. The composite solid electrolyte is also a composite solid electrolyte in which a specific inorganic sulfide material and a conductive polymer form a three-dimensional structure. As a result, the composite solid electrolyte obtained is in a form in which the surface of the inorganic sulfide material is coated and protected with the conductive polymer. As a result, the composite solid electrolyte of the present invention has low interface resistance, high conductivity, and excellent stability due to the synergistic effect between the inorganic sulfide material and the conductive polymer. [Brief description of the drawings]

[0023] [Figure 1(a)] FIG. 1 is a diagram showing the relationship between a conventional inorganic solid electrolyte and electrodes. [Figure 1(b)] 1 is a diagram showing the relationship between the composite solid electrolyte of the present invention and electrodes. [Diagram 2] FIG. 1 is a diagram showing the measurement results of internal interface resistance. [Diagram 3] 1 shows the results of measuring the capacity and cycling stability of a solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] (composite solid electrolyte) The composite solid electrolyte of the present invention is a three-dimensional structure of an inorganic sulfide material having ion conductivity containing sodium ions and a conductive polymer. FIG. 1 is a diagram for explaining a conventional inorganic solid electrolyte and the composite solid electrolyte of the present invention. FIG. 1(a) is a diagram showing the relationship between conventional inorganic solid electrolyte particles 11-13 and an electrode 14. As can be seen from FIG. 1(a), the conventional inorganic solid electrolyte transports Na ions 10 in the inorganic solid. Therefore, contact resistance occurs between the inorganic solid electrolyte particles 11-13, and interface resistance occurs between the electrode 14 and the inorganic solid electrolyte particle 13 in contact with the electrode. Therefore, there are problems in that the movement of Na ions 10 is restricted and the mechanical strength is also poor.

[0025] FIG. 1(b) is a diagram showing the relationship between the composite solid electrolyte of the present invention and the electrodes. As can be seen from FIG. 1(b), in the composite solid electrolyte of the present invention, the surfaces of the inorganic sulfides 21-23 are coated and protected with a conductive polymer 24. This makes it possible to suppress the decomposition reaction of the inorganic sulfides 21-23. In addition, a good adhesive interface can be constructed between the active material of the electrode 25 and the inorganic sulfide 23, which is a solid electrolyte. As a result, the interface resistance between the electrode and the electrolyte is reduced, and Na ions 20 can be moved well. In other words, a sodium ion battery with high performance and excellent stability can be obtained.

[0026] (Inorganic sulfide material with ionic conductivity containing sodium ions) The inorganic sulfide material containing sodium ions and having ionic conductivity used in the present invention has a composition containing Na, P, and S elements (sulfide containing Na-PS elements).

[0027] The inorganic sulfide material having ionic conductivity containing sodium ions is a compound represented by the following formula (I). NaM1M2PS····(I) In the formula, M1 and M2 are different elements, and are III-VI transition metals and metals of groups 13-15. Specific examples of M1 include Sb, Bi, La, Sr, and Zr. Specific examples of M2 include Sn, Ge, Al, and Ti.

[0028] The compound represented by formula (I) is preferably a compound represented by formula (I'). Na x M1 p M2 q P.S. y ...(I´) In formula (I'), x and y are numbers that satisfy 3≦x≦17 and 2≦y≦14, respectively. In addition, p and q are numbers that satisfy 0.01≦p≦10 and 0.001≦q≦10, respectively.

[0029] An inorganic sulfide material having ionic conductivity containing sodium ions can be obtained as a sulfide-based glass corresponding to the above formula (I) or formula (I') by subjecting a plurality of elements or molecules to mechanical milling.

[0030] In addition to sulfides containing Na, P, and S elements, sodium salts and metal oxides that improve electrical conductivity may be included. Examples of metal oxides that improve electrical conductivity include TiO 2 , SnO 2 , Al 2 O 3 , NiO 2 , W 2 O 3 etc.

[0031] (Conductive Polymer) The conductive polymer is a polymeric compound having high electrical conductivity. As the conductive polymer of the present invention, it is preferable to use a known conductive polymer such as a polymer having a polyethylene oxide main skeleton or a polyvinylidene fluoride resin.

[0032] Examples of polymers having polyethylene oxide as the main skeleton include polyethylene oxide (PEO), polyethylene glycol (PEG), polyphenylene oxide (PPO), acrylic / methacrylic resin (PMMA), polypropylene carbonate (PPC), etc. Examples of polyvinylidene fluoride resins include polyvinylidene fluoride (PVDF), etc.

[0033] PVDF may contain heterogeneous bonds represented by -CH-CF-CF-CH- and -CF-CH-CH-CF- in addition to the normal bonds represented by -CH-CF-CH-CF- in the molecular chain. It may also be a copolymer of these resins.

[0034] In addition to the above-mentioned conductive polymers, for example, polyvinylidene chloride (PVDC), polyacrylonitrile (PAN), and the like can also be used.

[0035] The composite solid electrolyte of the present invention is defined as a composite solid electrolyte of a sulfide having a three-dimensional network structure and a conductive polymer. The composite solid electrolyte of the present invention is classified into a chemically crosslinked gel (e.g., polyethylene oxide (PEO) etc.) that forms a gel structure by crosslinking points by chemical bonds, and a physically crosslinked gel (e.g., poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) etc.) that forms a gel structure by using microcrystals or the like as crosslinking points, depending on how the three-dimensional network structure is formed. Either a chemically crosslinked gel or a physically crosslinked gel may be used.

[0036] In the composite solid electrolyte of the present invention, the inorganic sulfide material and the conductive polymer may be mixed in any ratio. Even if a small amount of the conductive polymer is added, a three-dimensional network structure can be formed.

[0037] (Method of manufacturing composite solid electrolyte) The composite solid electrolyte of the present invention is produced, for example, as follows.

[0038] The method for producing a sulfide-based solid electrolyte of the present invention is characterized by a raw material composition preparation step of preparing a raw material composition containing at least sulfur (S), and a vitrification step of synthesizing a sulfide-based glass by subjecting the raw material composition to mechanical milling.

[0039] In the method for producing a sulfide-based solid electrolyte of the present invention, first, a raw material such as sodium phosphorus sulfide (Na 2 S) and phosphorus pentasulfide (P 2 S 5 ) and tin sulfide (SnS 2 ) and antimony sulfide (SbS 2 ) is prepared. Two or three types of metal sulfides are preferably used. The metal sulfides are mixed in a predetermined ratio to prepare a raw material composition. The mixing ratio may be appropriately adjusted depending on the raw materials used, and is, for example, 60:20:10:10.

[0040] Next, the raw material composition and grinding balls are put into a pot for mechanical milling, and the pot is sealed. Next, this pot is attached to a planetary ball mill, and milling is performed at room temperature for several minutes at low speed (for example, rotation speed: 100 ppm) to thoroughly mix the raw material composition. Next, the rotation speed is gradually increased (for example, 600 rpm), and milling is performed at this rotation speed for 15 hours to amorphize the raw material composition and synthesize powdered sulfide-based glass.

[0041] Next, the powdered sulfide-based glass was fired at about 300°C under an argon atmosphere to obtain powdered sulfide-based glass ceramics (Na 11 Sn 2-z Sb x P.S. 12) is synthesized. A conductive polymer is added to the obtained powdered sulfide-based glass ceramics to form a composite, and the desired sulfide-polymer composite solid electrolyte is obtained. In addition to the conductive polymer, metal oxides, metal phosphides, and metal fluorides can also be added.

[0042] The content of the compound in the raw material composition is not particularly limited, and is preferably selected appropriately depending on the composition of the intended sulfide-based solid electrolyte. For example, 2 S and P 2 S 5 and SnS 2 and Sb 2 S 3 In the present invention, when the 2 S and P 2 S 5 and SnS 2 and Sb 2 S 3 However, it is preferable that the molar ratio of these components satisfies the relationship of 60:20:10:10. As a result, a sulfide-based solid electrolyte having excellent Na ion conductivity can be obtained.

[0043] The composite solid electrolyte of the present invention can be mass-produced by using a mechanical milling method. In addition, a solid electrolyte having a three-dimensional network structure and high ionic conductivity can be obtained by adding a conductive polymer to a powdered sulfide-based glass ceramic and compounding the resulting mixture.

[0044] (battery) The composite solid electrolyte of the present invention can be used in an all-solid-state sodium battery, which includes at least a positive electrode, a positive electrode active material, a composite solid electrolyte, a negative electrode active material, and a negative electrode.

[0045] As the positive electrode active material and the negative electrode active material, known materials used in sodium solid state batteries can be used.

[0046] As the positive electrode active material, for example, p2 type Na 2 / 3 MeO 2(Me is a transition metal oxide), O3-based NaMeO 2 (Me transition metal oxide), etc. can be used. Specifically, Na 2 FeS 2 , NaCrO 2 , Na 2 FePO 4 F, NaFeO 2 -NaNi 0.5 Mn 0.5 O 2 、NaFeO 2 、Na1+xZr2(SiO4)x(PO4)3-x (x is a number satisfying 1.8 < x < 2.2), etc. can be mentioned.

[0047] As the negative electrode active material, for example, hard carbon, Sn, Sb, Sb 2 O 3 , Pb, P, Na 2 Ti 3 O 7 , TiO 2 , etc. can be mentioned.

Examples

[0048] The present invention will be described in detail based on examples below. The scope of the present invention is not limited to the examples.

[0049] (Example 1) As starting materials, sodium sulfide crystal (Na 2 S) and phosphorus pentasulfide (P 2 S 5 ) and SnS 2 and Sb 2 S 3 (each manufactured by Fujifilm Wako Pure Chemical Corporation) were used. 2 g of these powders were weighed in a dry box under an argon atmosphere at a molar ratio of 60:20:10:10 and put into a 60 ml zirconia pot (model number 4-3925-0, manufactured by AS ONE Corporation). Next, 8 g of dehydrated heptane was weighed and put into the above pot. Furthermore, zirconia grinding balls (model number 5-4060-34, manufactured by AS ONE Corporation) (φ10 mm, 20 g) were put into the above pot, and the pot was completely sealed.

[0050] The pot was attached to a planetary ball mill and milled at a low speed (rotation speed: 100 ppm) for a few minutes in the beginning to thoroughly mix the raw material composition. After that, the rotation speed was gradually increased and mechanical milling was performed at 600 rpm for 15 hours. Then, the pot was heated in an Ar atmosphere at 300°C for 2 hours to obtain Na 10 SnSbPS 12 After that, 10 ml of a liquid precursor containing poly(vinylidene fluoride-co-hexafluoropropylene) PVDF-HFP (Merck) copolymerized with hexafluoropropylene (HFP) and NaPF6 was added to the powder, and the mixture was dried to obtain a composite electrolyte.

[0051] As a comparative example, an inorganic sulfide-type solid electrolyte was prepared from the Na10SnSbPS12 powder obtained above, and a polymer-type solid electrolyte was prepared from PVDF-HFP and NaPF6.

[0052] [Evaluation 1] Electrical conductivity The composite electrolyte obtained in Example 1 was mixed with 6 t / cm 2 The mixture was pressed at 100° C. and molded into a pellet. The electrical conductivity (Na ion conductivity) of the obtained pellet was then measured by an AC two-terminal method. As a result, the electrical conductivity (room temperature (25° C.)) of the pellet using the powdered glass obtained in Example 1 was 2.6×10 -3 S / cm, and at 40°C, it is 1.0×10 -2 S / cm, and at 60°C, it is 2.5×10 -2 It was S / cm.

[0053] For comparison, the electrical conductivity of a pellet using a sulfide-type solid electrolyte (at room temperature (25°C)) was 1.2 x 10 -3 S / cm, and at 40°C, it is 4.5×10 -3 S / cm, and at 60°C, it is 9.3×10 -3 The electrical conductivity of the pellet using the polymer-type solid electrolyte (at room temperature (25°C)) was 2.8×10 -4 S / cm, and at 40°C, it is 3.2 x 10 -3S / cm, at 60°C, 2.2×10 -4 It was S / cm.

[0054] The above results are summarized in Table 1 below.

[0055] [Table 1]

[0056] From the above, it was found that the composite electrolyte of Example 1 had higher electrical conductivity than the conventional sulfide-type electrolytes and polymer-type electrolytes at all measurement temperatures.

[0057] [Evaluation 2] Internal interface resistance An all-solid-state battery was produced using the composite electrolyte, sulfide-type solid electrolyte, and polymer-type solid electrolyte obtained in Example 1. First, the composite electrolyte, sulfide-type solid electrolyte, and polymer-type solid electrolyte obtained in Example 1 were used, and Na foil was used as the electrode. 2 FePO 4 A three-layer pellet with a diameter of 9 mm and a thickness of 1.2 mm was formed by pelletizing the solid electrolyte and Na foil in order using a pellet mold. The pellet-shaped all-solid-state battery thus formed was housed in a stainless steel battery case with a diameter of 12 mm and a thickness of 1.6 mm. A battery lid was inserted into the battery case via a gasket, and the opening of the battery case was press-sealed to produce a coin-type battery. The battery thus produced was charged to 3.7 V at a current value of 150 μA, and the internal impedance of the coin-type battery after charging was examined by the AC impedance method using a potentiostat (HA-151B, Hokuto Denko Corporation). The results are shown in Figure 2.

[0058] 2, it was found that the internal interface resistance was much lower when the composite electrolyte of Example 1 was used than when the sulfide electrolyte or the polymer electrolyte was used alone. Moreover, the internal interface resistance of the composite electrolyte of Example 1 was lower than that of the combination of the sulfide electrolyte and the polymer electrolyte. This is believed to be because the composite electrolyte of Example 1 forms a three-dimensional structure.

[0059] [Evaluation 3] Capacity and cycling stability of solid-state batteries An all-solid-state battery was prepared as follows. The composite electrolyte, sulfide-type solid electrolyte, and polymer-type solid electrolyte obtained in Example 1 were used. A coin-type battery was prepared in the same manner as in Evaluation 2, using the positive electrode mixture, solid electrolyte, and hard carbon negative electrode. The capacity and cycling stability of the prepared battery were measured using a charge / discharge system battery charge / discharge device (HJ1001SD8C, manufactured by Hokuto Denko Corporation). The battery capacity and cycling stability are shown in FIG. 3. The battery using the composite electrolyte had the highest battery capacity. In addition, it was confirmed that the battery using the composite electrolyte in Example 1 had excellent stability after 200 cycles compared to the sulfide-type electrolyte and polymer-type electrolyte.

[0060] From the above, it was found that the composite electrolyte of the present invention has low interfacial resistance, high conductivity and excellent stability due to the synergistic effect of the inorganic sulfide material and the conductive polymer. [Explanation of symbols]

[0061] 10, 20 Na ions 11, 12, 13 Inorganic solid electrolyte particles 14, 25 electrodes 21, 22, 23 Inorganic sulfides 24 Conductive Polymers

Claims

1. A composite solid electrolyte comprising an inorganic sulfide material having ionic conductivity including sodium ions and a conductive polymer.

2. The composite solid electrolyte according to claim 1, wherein the inorganic sulfide material having ionic conductivity containing sodium ions contains Na-P-S elements.

3. The composite solid electrolyte according to claim 1, wherein the inorganic sulfide material having ionic conductivity containing sodium ions is a compound represented by the following formula (I): NaM1M2PS...(I)

4. The composite solid electrolyte according to claim 3 , wherein the compound represented by formula (I) is a compound represented by the following formula (I′): <h2 style=";text-align:left;direction:ltr">Na<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> 11<h2 style=";text-align:left;direction:ltr"> p <h2 style=";text-align:left;direction:ltr"> 12<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> 55<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> I'm sorry (3≦x≦17, 2≦y≦14, 0.01≦p≦10, 0.001≦q≦10)

5. 2. The composite solid electrolyte according to claim 1, wherein the conductive polymer is a polymer having a polyethylene oxide main skeleton or a polyvinylidene fluoride resin.

6. The composite solid electrolyte according to claim 1 , wherein the composite solid electrolyte is a three-dimensional structure of the inorganic sulfide material and the conductive polymer.

7. A battery comprising the composite solid electrolyte according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Electrolyte composition, sheet and battery

    JP2022145417A